Formation of Zn2sio4:Co2+ Solid Solutions in The Coo-Zno-Sio2 System: Phase Formation and Colorimetric Characteristics - Kodirova Umida Aslonovna; Kadyrova Zulayho Raimovna; Usmanov Khikmatulla Lutpullayevich; Khomidov Fakhriddin Gafurovich; Eminov Azizjon Аshrapovich; Tairov Saidamir Saidmalikovich (Emerging Frontiers Library for The American Journal of Applied Sciences, 2026)
The study examines the synthesis and color characteristics of Co-containing ceramic pigments in the CoO-ZnO-SiO2 system. Pigments were prepared from Zn(NO3)2·6H2O, Co(NO3)2·6H2O, and quartz sand (SiO2) by solid-state firing in air at 1050-1250 °C. X-ray diffraction confirmed willemite-type Zn₂SiO₄ as the main phase; at 1050 °C secondary phases (Co2SiO4, α-SiO2, and traces of ZnO) were detected, while their contribution decreased markedly with increasing temperature, indicating near-complete willemite formation at 1250 °C. Diffuse reflectance colorimetry (CIELAB, D65/10°) showed progressive darkening and saturation of the blue–violet color with temperature (L* 58.57→33.43; b* -38.35→-48.65; C* 39.15→49.25) with an almost constant hue angle. The most stable and intense coloration was achieved at 1250 °C (ΔE* vs 1250 °C: 27.17 at 1050 °C and 9.78 at 1150 °C).